The palmaris profundus, a rare sight during carpal tunnel release - Browne, K. M. (Hand (N Y), 2014)
Palmaris profundus is a rare anatomical anomaly that may complicate carpal tunnel release. We discuss a recent case of carpal tunnel syndrome and its surgical release, whilst reviewing the published anatomical and surgical literature.